Development of Classical Guidance Service Based on Social and Emotional Learning (SEL) to Improve the Intrapersonal Aspects of Student’s Learning - Ma’mun, Sukron; Hartinah, Siti; Sudibyo, Hanung (Journal of English Language and Education, 2025)
This study aims to: (1) identify students' needs for classical guidance services based on Social and Emotional Learning (SEL) in improving intrapersonal learning, (2) design the development of classical guidance services based on SEL, (3) test the effectiveness of these services in improving students' intrapersonal learning aspects at MAN 1 Tegal City. This study uses a research and development method with the ADDIE model from Dick and Carey. Data collection techniques include questionnaires, observations, validation sheets, interviews, literature studies, and documentation. The study population consisted of 482 class XI students of MAN 1 Tegal City, which were divided into control classes and experimental classes. Data analysis was carried out through normality tests, validity, reliability, t-tests, and media feasibility and effectiveness tests. The results of the study indicate that the classical guidance service module based on SEL has a significant effect on improving students' intrapersonal skills. Analysis of teacher and student needs includes media selection, format, compilation of questions and answers, and design of media applications. Validation from three experts showed that the material aspect scored 90.62%, while the media aspect reached 93.75%. The effectiveness of the module was proven by the increase in student learning outcomes, where the pre-test score of the experimental class increased from 13.89% to 83.34% in the post-test. These results confirm that the SEL-based classical guidance service module has a positive impact on students' intrapersonal skills in learning.